A perovskite precursor solution, preparation method and application

By adding carbonol to the precursor solution of the perovskite to adjust the Moorby to accelerate the transformation of the black phase in the middle, the black phase CSPBI3 thin film crystalline crystallization and high deficiency density have been solved. Essence

CN114975656BActive Publication Date: 2025-01-24HUBEI UNIV OF ARTS & SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210629112.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-01
Publication Date
2025-01-24
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

In the preparation of the black phase CsPbI3 perovskite film, the intermediate phase is difficult to transform into the black phase, resulting in the problem of low crystallinity and high defect density.

Method used

By adding carbinol to the precursor solution of the perovantic ore, the Moore ratio of CSPBI3 and carbonate is 1: (0.01 ~ 0.02) to accelerate the transformation of the black phase in the middle.

Benefits of technology

The black phase CSPBI3 inorganic perovskite film with good appearance, high crystallization, and low deficiency density has been realized, simplifying the process conditions and reducing production difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114975656B_ABST
    Figure CN114975656B_ABST
Patent Text Reader

Abstract

The present invention provides a perovskite precursor solution, a preparation method and an application. The present invention provides a perovskite precursor solution, wherein the perovskite precursor solution comprises carbohydrazide and CsPbI3, and the molar ratio of the CsPbI3 to the carbohydrazide is 1:(0.01-0.02). Compared with the prior art, in the present invention, by adding carbohydrazide to CsPbI3 to obtain a perovskite precursor solution, the transformation of the intermediate phase to the black phase is accelerated, and the adverse effects of external factors on the film surface are reduced, thereby preparing a CsPbI3 inorganic perovskite film with good morphology, high crystallinity and low defect density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of perovskite batteries, and in particular relates to a perovskite precursor solution, a preparation method and an application thereof. Background Art

[0002] Organic-inorganic hybrid perovskite solar cells (PSCs) have achieved great progress in photoelectric conversion efficiency due to their outstanding optoelectronic properties. However, the insufficient stability of organic-inorganic hybrid perovskite materials due to thermal degradation or phase aggregation remains a huge obstacle to commercialization. Recently, all-inorganic perovskites without volatile organic cations have attracted widespread attention due to their remarkable thermal stability. Typically, black-phase CsPbI3 perovskites with a suitable bandgap (1.7 eV) can be used as top cells in series with silicon solar cells to further improve the device performance of silicon or perovskite solar cells.

[0003] In addition, CsPbI3 perovskite avoids phase separation like mixed halogen perovskite, and it has outstanding light stability. These advantages make CsPbI3 perovskite solar cells occupy an important position in commercial applications. In the past few years, CsPbI3 perovskite solar cells have made significant progress, and the efficiency has exceeded 20%. On the one hand, the intermediate phase is introduced to regulate its nucleation and crystallization process, and on the other hand, the thin film surface passivation strategy is adopted to reduce the defect state density.

[0004] However, in the process of preparing black phase CsPbI3 perovskite, it is difficult for the intermediate phase to transform into the black phase. Even after a long reaction process, the crystal phase characteristics of the transformed black phase are still not obvious. Summary of the invention

[0005] In view of this, the present invention provides a perovskite precursor solution, a preparation method and an application to accelerate the transformation of the intermediate phase to the black phase and reduce the adverse effects of the external environment on the film surface, thereby preparing a black phase CsPbI3 inorganic perovskite film with good morphology, high crystallinity and low defect density.

[0006] To achieve the above object, the present invention provides a perovskite precursor solution, which includes carbohydrazide and CsPbI3, and the molar ratio of CsPbI3 to carbohydrazide is 1:(0.01-0.02).

[0007] Optionally, in the perovskite precursor solution, the concentration of CsPbI3 is 0.3 mol / L to 1.0 mol / L; and / or,

[0008] The solvent of the perovskite precursor solution is dimethylformamide.

[0009] In addition, the present invention also provides a method for preparing the above-mentioned perovskite precursor solution, comprising the following steps:

[0010] Carbohydrazide and CsPbI3 are added into a solvent and mixed to obtain the perovskite precursor solution.

[0011] Optionally, the step of adding carbohydrazide and CsPbI3 into a solvent and mixing them to obtain the perovskite precursor solution comprises:

[0012] Dimethylamine hydroiodide, PbI2, CsI and carbohydrazide are mixed and added into the solvent, and shaken to obtain the perovskite precursor solution.

[0013] In addition, the present invention also provides a perovskite battery, comprising a substrate, an electron transport layer, a perovskite active layer, a hole transport layer and an electrode stacked in sequence, wherein the perovskite active layer is deposited from the above-mentioned perovskite precursor solution.

[0014] Optionally, the substrate is made of FTO conductive glass; and / or,

[0015] The electron transport layer is made of TiO2; and / or

[0016] The material of the hole transport layer is Spiro-OMeTAD; and / or,

[0017] The material of the electrode is Au; and / or,

[0018] The thickness of the electrode is 60-80 nm.

[0019] In addition, the present invention also provides a method for preparing the above-mentioned perovskite battery, comprising the following steps:

[0020] providing a substrate;

[0021] coating an electron transport layer on the substrate;

[0022] depositing a perovskite active layer on the electron transport layer;

[0023] depositing a hole transport layer on the perovskite active layer;

[0024] An electrode layer is deposited on the hole transport layer.

[0025] Optionally, the step of providing a substrate comprises: washing the FTO conductive glass in deionized water, anhydrous ethanol, acetone and isopropyl ketone in sequence and then drying; and / or,

[0026] The step of coating the electron transport layer on the substrate comprises: spin coating a titanium n-butoxide solution on the pretreated conductive glass FTO surface, and then annealing at 100 to 120° C. for 7 to 10 minutes to form the electron transport layer; and / or,

[0027] The step of depositing a perovskite active layer on the electron transport layer comprises: spin coating the perovskite precursor solution on the surface of the electron transport layer, annealing at 200° C. to 220° C. for 3 minutes to 10 minutes, and cooling to room temperature to obtain the perovskite active layer; and / or,

[0028] The step of depositing an electrode layer on the hole transport layer comprises:

[0029] Au is deposited on the surface of the hole transport layer by a thermal evaporation method to obtain the electrode layer.

[0030] In addition, the present invention also provides the use of carbohydrazide, the above-mentioned perovskite precursor solution, the above-mentioned method of preparing the perovskite precursor solution or the above-mentioned method for preparing the perovskite battery in promoting the formation of a black phase CsPbI3 perovskite film.

[0031] Compared with the prior art, in the present invention, by adding carbohydrazide to CsPbI3 to obtain a perovskite precursor solution, the transformation of the intermediate phase to the black phase is accelerated, and the adverse effects of external factors on the film surface are reduced, thereby preparing a CsPbI3 inorganic perovskite film with good morphology, high crystallinity and low defect density. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is a diagram of the structure of a perovskite battery;

[0034] Figure 2 The flowchart of the preparation of the perovskite battery of the present invention is as follows;

[0035] Figure 3 The XRD test result diagram of the perovskite active layer of the perovskite battery of Examples 1 to 2 and Comparative Examples 1 to 3;

[0036] Figure 4 The XRD test results of the perovskite active layer in different time periods after annealing in Example 1 and Comparative Example 1 are shown;

[0037] Figure 5The appearance observation diagram of the perovskite film after annealing in Example 1 and Comparative Example 1 over a period of time;

[0038] Figure 6 The SEM images of the perovskite films of the batteries of Examples 1 to 2 and Comparative Examples 1 to 3 are taken.

[0039] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0040] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0041] It should be noted that, in the embodiments, those without specifying specific conditions are carried out according to normal conditions or conditions recommended by the manufacturer. Those without specifying the manufacturer of reagents or instruments used are conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, and "A and / or B" is taken as an example, including schemes A, B, or A and B that meet the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of the technical schemes is contradictory or cannot be achieved, it should be considered that the combination of such technical schemes does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work, all belong to the scope of protection of the present invention.

[0042] In view of the technical defects of the existing CsPbI3 inorganic perovskite film in the prior art, such as low crystallinity and slow black phase conversion, the present invention provides a perovskite precursor solution, wherein the perovskite precursor solution comprises carbohydrazide and CsPbI3, and the molar ratio of the CsPbI3 to the carbohydrazide is 1:(0.01-0.02).

[0043] Regarding the transformation of the intermediate phase CsPbI3 to the black phase, existing research believes that the key to its process is mainly concentrated in the crystal phase transformation process. Therefore, the main research and development ideas of the existing technology for promoting the black phase are mainly to control the regulation of the crystal phase transformation process, such as adjusting the annealing temperature, such as fine-tuning in the process of generating the crystal phase. These are all focused on controlling strict production control conditions or frequent operation adjustments. The production difficulty is relatively large, which is definitely not conducive to its expanded production. In the process of the inventor's research team on the new CsPbI3 perovskite thin film battery, it was accidentally discovered that the CsPbI3 perovskite precursor solution with the addition of carbohydrazide can promote its black phase transformation and control its reaction before crystallization control. Its operation is simpler and more helpful for its industrial application.

[0044] Compared with the prior art, in the present invention, by adding carbohydrazide to CsPbI3 to obtain a perovskite precursor solution, the transformation of the intermediate phase to the black phase is accelerated, and the adverse effects of external factors on the film surface are reduced, thereby preparing a CsPbI3 inorganic perovskite film with good morphology, high crystallinity and low defect density. It has been found through research that after excessive addition of CsPbI3, it does not promote the formation of the black phase, and when insufficient amount of carbohydrazide is added, its promoting effect cannot be reflected.

[0045] It should be noted that while satisfying the molar ratio, the concentration of CsPbI3 can be adjusted according to actual conditions. Specifically, in some embodiments of the present invention, in the perovskite precursor solution, the concentration of CsPbI3 is 0.3 mol / L to 1.0 mol / L; accordingly, under the premise of satisfying the dispersion of solutes and subsequent removal, the choice of solvent for the perovskite precursor solution is not particularly limited. In some embodiments of the present invention, the solvent is dimethylformamide.

[0046] In addition, the present invention also provides a method for preparing the above-mentioned perovskite precursor solution, comprising the following steps: adding carbohydrazide and CsPbI3 to a solvent and mixing them to obtain the perovskite precursor solution. The above method can be used to prepare a perovskite precursor solution with a fast-transforming CsPbI3 black phase film. Specifically, any raw material can be selected to compound into a molecular formula according to CsPbI3. Specifically, in the present invention, dimethylamine hydroiodide, PbI2, and CsI can be configured in a molar ratio of 1:1:1.

[0047] In addition, the present invention also provides a perovskite battery, such as Figure 1 As shown, it includes a substrate 1, an electron transport layer 2, a perovskite active layer 3, a hole transport layer 4 and an electrode 5 which are stacked in sequence, wherein the perovskite active layer is deposited from the above perovskite precursor solution.

[0048] In some embodiments, the substrate is made of FTO conductive glass; the FTO substrate is rougher, the electron layer is deposited more densely on it, and the FTO energy level is more matched.

[0049] In some embodiments, the electron transport layer is made of TiO2;

[0050] TiO2 can withstand higher temperatures than other electron transport layers such as SnO2, which will be destroyed by high temperatures at 180°C.

[0051] In some embodiments, the hole transport layer is Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene).

[0052] The hole transport capability and energy level of the hole transport layer Spiro-OMeTAD are more closely matched to the valence band of the perovskite, which is beneficial for hole extraction and reduces hole recombination.

[0053] In some embodiments, the electrode is made of Au;

[0054] Au has a stronger conductivity than Ag and is more compatible with the device structure energy level. In some embodiments, the thickness of the electrode is 60 to 80 nm. When the thickness is in this range, it is beneficial for the perovskite to absorb light.

[0055] In addition, if Figure 2 As shown, the present invention also provides a method for preparing the above-mentioned perovskite battery, comprising the following steps:

[0056] Step S10: providing a substrate;

[0057] Step S20: coating an electron transport layer on the substrate;

[0058] Step S30: depositing a perovskite active layer on the electron transport layer;

[0059] Step S40: depositing a hole transport layer on the perovskite active layer;

[0060] Step S50: depositing an electrode layer on the hole transport layer.

[0061] Through the above steps, a perovskite cell with a black phase CsPbI3 thin film can be prepared.

[0062] Step S10 includes: washing the FTO conductive glass in deionized water, anhydrous ethanol, acetone and isopropyl tone in sequence and then drying; through the above washing steps, pollution-free conductive glass can be prepared to avoid the adverse effects of pollutants on the conductive glass on battery performance.

[0063] Step S20 includes: spin coating a titanium n-butoxide solution on the pretreated conductive glass FTO surface, and then annealing at 100-120°C for 7-10 minutes to form the electron transport layer; when the spin coating is appropriate, when the temperature is higher than 120°C, the electron layer will be burned out, thereby failing to transmit photogenerated electrons; when the temperature is lower than 100°C, the electron layer is not dense enough, which will also cause the photogenerated electrons to fail to be transmitted.

[0064] Step S30 includes: spin coating the perovskite precursor solution on the electron transport layer, annealing at 200°C to 220°C for 3 minutes to 10 minutes, and cooling to room temperature to obtain the perovskite active layer; through this annealing condition, the transformation of the black phase of the perovskite precursor can be completed. If the temperature is too low, a large amount of transparent phase DMAPbI3 will be present inside the perovskite, which is not conducive to device performance. If the temperature is too high, a large number of holes will appear on the surface of the perovskite.

[0065] In step S40, a hole transport layer is added by spin coating.

[0066] In step S50, the step of depositing an electrode layer on the hole transport layer includes:

[0067] Au is deposited on the surface of the hole transport layer by thermal evaporation to obtain the electrode layer. This method can be used to deposit a uniform metallographic thin film to generate an electrode layer with excellent performance.

[0068] In addition, the present invention also provides the use of carbohydrazide, the above-mentioned perovskite precursor solution, the above-mentioned method for preparing the perovskite precursor solution or the above-mentioned method for preparing the perovskite battery in promoting the formation of a black phase CsPbI3 perovskite film. It has been verified that in the present invention, in the CsPbI3 solution, the formation of the black phase can be promoted by adding carbohydrazide. Of course, under this premise, the above-mentioned perovskite precursor solution, the above-mentioned method for preparing the perovskite precursor solution or the above-mentioned method for preparing the perovskite battery can all be used to promote the use of the black phase.

[0069] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0070] Embodiments 1 to 5

[0071] Embodiments 1 to 5 provide a perovskite battery, the specific structure of which is as follows Figure 2 As shown, it includes a FTO substrate 1, a TiO2 electron transport layer 2, a perovskite active layer 3, a Spiro-OMeTAD hole transport layer and an Au electrode 4 which are stacked in sequence.

[0072] The thickness of the electrodes is shown in Table 1.

[0073] Table 1 Electrode thickness of Examples 1 to 5

[0074] Electrode thickness (nm) Example 1 60 Example 2 70 Example 3 80 Example 4 75 Example 5 65

[0075] Example 6

[0076] This embodiment provides a method for preparing the perovskite battery of embodiment 1, comprising the following steps:

[0077] (1) The FTO conductive glass was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropyl ketone for 15 min each, and finally dried with nitrogen gas for later use.

[0078] (2) A titanium n-butoxide solution with a concentration of 0.2 M was spin-coated on the pretreated conductive glass FTO surface at a rate of 2000 rpm / s to 4000 rpm, and the spin coating was performed for 30 seconds. The solution was annealed at 100° C. for 10 minutes to generate an electron transport layer.

[0079] (3) DMAI (dimethylamine hydroiodide), PbI2, CsI and carbohydrazide were dissolved in DMF solution and shaken thoroughly at room temperature for 2-4 hours to form a 0.6 M CsPbI3 precursor solution. The molar ratio of DMAI: PbI2: CsI: carbohydrazide was 1:1:1:0.01.

[0080] (4) Spin coating the CsPbI3 perovskite precursor solution on the surface of the electron transport layer and annealing at 210°C for 5 min to generate a perovskite active layer.

[0081] (5) Depositing Au metal electrode on the surface of the hole transport layer.

[0082] Example 7

[0083] This embodiment provides a method for preparing a perovskite battery according to embodiment 2, comprising the following steps:

[0084] (1) The FTO conductive glass was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropyl ketone for 20 min each, and finally dried with nitrogen for later use.

[0085] (2) A titanium n-butoxide solution with a concentration of 0.3 M was spin-coated on the pretreated conductive glass FTO surface at a rate of 3000 rpm / s to 4500 rpm, and the spin coating was performed for 35 seconds. The solution was annealed at 110°C for 8 minutes to generate an electron transport layer.

[0086] (3) DMAI, PbI2, CsI and carbohydrazide were dissolved in DMF solution and shaken thoroughly at room temperature for 2-4 h to form a 0.8 M CsPbI3 precursor solution, with a molar ratio of DMAI: PbI2: CsI: carbohydrazide of 1:1:1:0.02.

[0087] (4) Spin coating the CsPbI3 perovskite precursor solution on the surface of the electron transport layer and annealing at 200°C for 7 min to generate a perovskite active layer.

[0088] (5) Depositing Au metal electrode on the surface of the hole transport layer.

[0089] Example 8

[0090] This embodiment provides a method for preparing a perovskite battery according to embodiment 3, comprising the following steps:

[0091] (1) The FTO conductive glass was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropyl ketone for 20 min each, and finally dried with nitrogen for later use.

[0092] (2) A titanium n-butoxide solution with a concentration of 0.15 M was spin-coated on the pretreated conductive glass FTO surface at a rate of 2500 rpm / s to 4000 rpm, and the spin coating was performed for 30 seconds. The solution was annealed at 120°C for 8 minutes to generate an electron transport layer.

[0093] (3) DMAI, PbI2, CsI and carbohydrazide were dissolved in DMF solution and shaken thoroughly at room temperature for 2-4 h to form a 0.5 M CsPbI3 precursor solution, with a molar ratio of DMAI: PbI2: CsI: carbohydrazide of 1:1:1:0.015.

[0094] (4) Spin coating the CsPbI3 perovskite precursor solution on the surface of the electron transport layer and annealing at 180°C for 9 minutes to generate a perovskite active layer.

[0095] (5) Depositing Au metal electrode on the surface of the hole transport layer.

[0096] Example 9

[0097] This embodiment provides a method for preparing a perovskite battery according to embodiment 4, comprising the following steps:

[0098] (1) The FTO conductive glass was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropyl ketone for 20 min each, and finally dried with nitrogen for later use.

[0099] (2) A titanium n-butoxide solution with a concentration of 0.25 M was spin-coated on the pretreated conductive glass FTO surface at a rate of 2000 rpm / s to 4000 rpm, and the spin coating was performed for 40 seconds. The solution was annealed at 120°C for 8 minutes to generate an electron transport layer.

[0100] (3) DMAI, PbI2, CsI and carbohydrazide were dissolved in DMF solution and shaken thoroughly at room temperature for 2 to 4 h to form a 0.5 M CsPbI3 precursor solution with a molar ratio of DMAI: PbI2: CsI: carbohydrazide of 1:1:1:0.018.

[0101] (4) Spin coating the CsPbI3 perovskite precursor solution on the surface of the electron transport layer and annealing it at 200°C for 6 min to generate a perovskite active layer.

[0102] (5) Depositing Au metal electrode on the surface of the hole transport layer.

[0103] Example 10

[0104] This embodiment provides a method for preparing a perovskite battery according to embodiment 5, comprising the following steps:

[0105] (1) The FTO conductive glass was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropyl ketone for 20 min each, and finally dried with nitrogen for later use.

[0106] (2) A titanium n-butoxide solution with a concentration of 0.25 M was spin-coated on the pretreated conductive glass FTO surface at a rate of 3000 rpm / s to 4000 rpm, and the spin coating was performed for 30 seconds. The solution was annealed at 120°C for 8 minutes to generate an electron transport layer.

[0107] (3) DMAI, PbI2, CsI and carbohydrazide were dissolved in DMF solution and shaken thoroughly at room temperature for 2-4 h to form a 0.5 M CsPbI3 precursor solution, with a molar ratio of DMAI: PbI2: CsI: carbohydrazide of 1:1:1:0.015.

[0108] (4) Spin coating the CsPbI3 perovskite precursor solution on the surface of the electron transport layer and annealing at 200°C for 7 min to generate a perovskite active layer.

[0109] (5) Depositing Au metal electrode on the surface of the hole transport layer.

[0110] Comparative Example 1

[0111] This comparative example provides a perovskite battery, whose structure and preparation method are substantially the same as those of Example 1, except that no carbohydrazide is added.

[0112] Comparative Examples 2-3

[0113] Comparative Examples 2 to 3 respectively provide a perovskite battery, whose structure and preparation method are generally consistent with Example 1. The only difference in Comparative Example 2 is that the molar ratio of carbohydrazide to CsPbI3 is 3%, and the only difference in Comparative Example 3 is that the molar ratio of carbohydrazide to CsPbI3 is 6%.

[0114] Test Examples

[0115] 1. The perovskite active layer of the perovskite battery of Examples 1 to 2 and Comparative Examples 1 to 3 is subjected to XRD detection, wherein the XRD test of the same time period after annealing is as follows: Figure 3 As shown, the XRD patterns of Example 1 and Comparative Example 1 at different time periods after annealing are as follows: Figure 4 As shown. Figure 3 It can be seen that in the same time period, the molar ratio of carbohydrazide to CsPbI3 is in the range of 1% to 2%. Compared with Comparative Example 1 without carbohydrazide and Comparative Examples 2 to 3 with excessive addition, its crystal peak is sharper, indicating that its crystal form is more complete. Figure 4 It can be seen from the XRD test at different times that the XRD of Example 1 with carbohydrazide added has generated a standard black phase crystal peak within 1 minute, while Comparative Example 1 still has impurity peaks.

[0116] 2. The annealed perovskite films of Example 1 and Comparative Example 1 were observed simultaneously over a period of time. The appearance of the films changed over time as shown in the figure below: Figure 5 As shown, it can be seen that compared with Comparative Example 1 without adding carbohydrazide, the color of Example 1 is darker within 120s in the observation period, proving that the black phase conversion is more complete, wherein, Figure 5 In the figure, A is the conversion status of the perovskite film of Example 1, and B is the conversion status of the perovskite film of Comparative Example 1.

[0117] 3. The perovskite films of the batteries of Examples 1 to 2 and Comparative Examples 1 to 3 were subjected to SEM testing. The test results showed that Figure 6 As shown, compared with comparative examples 1 to 3, the perovskite films of embodiments 1 to 2 are denser and have no holes. Furthermore, the perovskite film of embodiment 1 has better appearance performance. Figure 6 In the figure, A is the SEM test result of comparative example 1, B is the test result of embodiment 1, C is the test result of embodiment 2, D is the test result of comparative example 2, and E is the test result of comparative example 3.

[0118] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A perovskite precursor solution, characterized in that: The perovskite precursor solution includes carbohydrazide and CsPbI3, and the molar ratio of the CsPbI3 to the carbohydrazide is 1:(0.01-0.02).

2. The perovskite precursor solution according to claim 1, characterized in that In the perovskite precursor solution, the concentration of CsPbI3 is 0.3 mol / L to 1.0 mol / L; and / or, The solvent of the perovskite precursor solution is dimethylformamide.

3. A method for preparing the perovskite precursor solution according to claim 1 or 2, characterized in that: The following steps are involved: Carbohydrazide and CsPbI3 are added into a solvent and mixed to obtain the perovskite precursor solution.

4. The method for preparing a perovskite precursor solution according to claim 3, characterized in that: The step of adding carbohydrazide and CsPbI3 into a solvent and mixing them to obtain the perovskite precursor solution comprises: Dimethylamine hydroiodide, PbI2, CsI and carbohydrazide are mixed and added into the solvent, and shaken to obtain the perovskite precursor solution.

5. A perovskite battery, characterized in that: The invention comprises a substrate, an electron transport layer, a perovskite active layer, a hole transport layer and an electrode which are stacked in sequence, wherein the perovskite active layer is deposited from the perovskite precursor solution according to any one of claims 1 to 4.

6. The perovskite battery according to claim 5, characterized in that: The material of the substrate is FTO conductive glass; and / or, The electron transport layer is made of TiO2; and / or The hole transport layer is made of Spiro-OMeTAD; and / or, The material of the electrode is Au; and / or, The thickness of the electrode is 60-80 nm.

7. A method for preparing a perovskite battery as claimed in claim 5 or 6, characterized in that: The following steps are involved: providing a substrate; coating an electron transport layer on the substrate; depositing a perovskite active layer on the electron transport layer; depositing a hole transport layer on the perovskite active layer; An electrode layer is deposited on the hole transport layer.

8. The method for preparing a perovskite battery according to claim 7, characterized in that: The step of providing a substrate comprises: washing the FTO conductive glass in deionized water, anhydrous ethanol, acetone and isopropyl ketone in sequence and then drying; and / or, The step of coating the electron transport layer on the substrate comprises: spin coating a titanium n-butoxide solution on the pretreated conductive glass FTO surface, and then annealing at 100 to 120° C. for 7 to 10 minutes to form the electron transport layer; and / or, The step of depositing a perovskite active layer on the electron transport layer comprises: spin coating the perovskite precursor solution on the surface of the electron transport layer, annealing at 200° C. to 220° C. for 3 minutes to 10 minutes, and cooling to room temperature to obtain the perovskite active layer; and / or, The step of depositing an electrode layer on the hole transport layer comprises: Au is deposited on the surface of the hole transport layer by a thermal evaporation method to obtain the electrode layer.

9. Use of carbohydrazide, the perovskite precursor solution as claimed in claim 1 or 2, the method for preparing a perovskite precursor solution as claimed in claim 3, or the method for preparing a perovskite battery as claimed in claim 7 in promoting the formation of a black phase CsPbI3 perovskite film.

Citation Information

Patent Citations

  • Full-printing mesoscopic perovskite solar cell taking aniline or azine ring as additive and preparation method thereof

    CN111146344A